Impacts of COVID-19 on management of IT projects - Tarja, Shkelzen; Kučera, Jan; Malcová, Dana; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The master thesis aims to analyze the impacts of the COVID-19 pandemic on IT projects and to study the responses of managers of IT projects to this crisis. To accomplish the thesis goal, a comprehensive literature review was performed. The main findings from the literature review were verified with the help of 18 project management specialists who participated in a semi-structured interview on the pandemic disruptions in IT project management. Based on the feedback from the chosen participants, a set of procedures on how to improve the resilience of IT projects was recommended, initially reviewed by three, and subsequently validated by nine project management specialists using an online survey. The central thesis output is the findings from the interview and the resilience improvement recommendations.
Vedoucí práce: Jan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses